EXPLORING CLASSROOM SPEAKING ACTIVITIES AT ENGLISH LANGUAGE EDUCATION STUDY PROGRAM OF KHAIRUN UNIVERSITY - Sasmita Pratiwi Anu; Sutaryo Sutaryo; Roswita Mubin Aboe (Cakrawala Bahasa, 2020)
This study aims to: 1) lecturers 'activities applied in the classroom and, 2) investigating the difficulties of lecturers in applying English in class, the instruments used are observation and interview results, the results of the study indicate that the lecturers' activities in the speaking class meet all proposed criteria in Flanders’s interaction analysis (FIAC) category which consists of three categories Lecturer activities applied in four semesters include all content in the Interaction Analysis Category Flanders (FIAC).  In which there are three categories of Indirect Talk, Direct Talk and Students Talk. There are lecturer activities starting from the beginning of the class until the end of class learning, such as receiving feelings, praise or encouragement, accepting or using student ideas, asking questions, teaching / give lectures, give direction, criticize or justify authority, student's speech response, student talk initiation, and silence / pause / confusion. From three categories and ten points lecturer one (L1) and lecturer two (L2) has been fulfilled class activities but L1 and L1 admitted that many students have lacked vocabulary in speaking therefore students did not confident in using English in class.